Evolution of virulence in Enterococcus faecium, a hospital-adapted opportunistic pathogen. (February 2018) - Gao, Wei; Howden, Benjamin P; Stinear, Timothy P
Highlights: Enterococcus faecium is gaining prominence as a nosocomial pathogen. Genome expansion is a distinguishing feature of health-care associated E. faecium . Virulence is linked to cell wall structures, secreted proteins, carbohydrate use. More research, better tools required to discover gene function in E. faecium . Abstract : Enterococci are long-standing members of the human microbiome and they are also widely distributed in nature. However, with the surge of antibiotic-resistance in recent decades, two enterococcal species ( Enterococcus faecalis and Enterococcus faecium ) have emerged to become significant nosocomial pathogens, acquiring extensive antibiotic resistance. In this review, we summarize what is known about the evolution of virulence in E. faecium, highlighting a specific clone of E. faecium called ST796 that has emerged recently and spread globally.